PENGARUH INDEPENDENSI, TIME BUDGET PRESSURE, TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI DENPASAR BALI, DENGAN ETIKA AUDITOR SEBAGAI MODERASI - Komang Gede Martin Sumiarta; Ni Wayan Alit Erlina Wati; Putu Nuniek Hutnaleonita (UNHI Press, 2021)
The objectives of this study are: (1) To determine the effect of independence on the audit quality of the Bali Public Accounting Firm (2) To determine the effect of time budget pressure on the audit quality of the Bali Public Accounting Firm. (3) Determine the ethical role of auditors in regulating the relationship between independence and audit quality. (4) Determine the role of auditor ethics in reducing the relationship between time budget pressure and audit quality. This research was conducted at a public accounting firm in Denpasar, Bali. The total sample size is 55 people. The sampling method used was non-probability sampling, namely purposive sampling, while the data analysis techniques were descriptive statistics, validity testing, reliability testing, and classical hypothesis testing. Moderated Regression Analysis (MRA) test, model feasibility test (F test), test partial (t test) and the coefficient of determination (R2). The results showed that: (1) Independence affects audit quality, where the regression coefficient value on the independence variable is recorded at 2.339 and the significance value (Sig.) Of 0.018 is less than 0.05. (2) Time budget pressure affects audit quality, where the regression coefficient value on the time budget pressure variable is recorded at -6.898 and the significance value (Sig.) Of 0.002 is less than 0.05. (3) The interaction of independence and auditor ethics can moderate audit quality, where the regression coefficient value on the interaction of independent variables and auditor ethics is recorded at -0.047 and the significance value (Sig.) Of 0.022 is less than 0.05. (4) The interaction of time budget pressure with auditor ethics can moderate audit quality, where the regression coefficient value on the interaction variable time budget pressure and auditor ethics is 0.141 and the significance value (Sig.) Of 0.003 is less than 0.05.